The dramatic role of astronomy in early modern drama - Coston, M (2017)
By examining five types of astronomical and celestial phenomena—comets, constellations, the zodiac, planets, and the music of the spheres—this thesis posits not only that early modern dramatists were influenced by established and emerging natural philosophy as habits of thought that manifested in their writing, but also that astronomical phenomena operate within the drama, performance, and in the theatre as elements for creating and developing a distinctly spatial dramaturgy. Using theories from the spatial turn, this thesis maps the positions, edges, disturbances, and motions of celestial properties within the imaginary and physical space of early modern drama and theatre. It argues that the case study plays examined within this thesis demonstrate a period-wide engagement, rather than an authorial-, company-, theatre-, or even genre-specific practice. Dramatists developed techniques using astronomical phenomena as dramatic methods that occasionally underscored early modern astronomical thought. However, in many cases constructed plots, characters, visual and sound effects, and movements transgressed astronomical expectations. Dramatists broke down constellations, inserted new stars in the heavens, created zodiacal females, launched pyrotechnical comets, moved planets unexpectedly across the stage, and played (and refrained from playing) celestial "music" for the audience. Recognising composite and often contradictory astronomical constructions within the drama, this thesis moves the critical discussion away from an intellectual history of natural philosophy and gravitates toward an active astronomical dramaturgy.